A Feasibility and Acceptability Study Using Ecological Momentary Assessment to Evaluate Drug Use Patterns Among Midwestern People Who Use Drugs - Tyler, Kimberly A. (Journal of drug issues, 2025)
We use a unique platform called the Open Dynamic Interaction Network (ODIN) app, to collect fine grained, daily data from participants. Our results graphically depict the feasibility of using the ODIN app with people who use drugs (PWUD) in the Great Plains. During fall 2022-spring 2023, 100 participants (53% female), using an Android smartphone with the ODIN app installed, were asked up to 22 questions per day on substance use, stress, and social support over 30 days. The mean overall daily response rates to the ecological momentary assessment questions using the ODIN app was 82%. Overall, 82% of participants reported that the ODIN app was “somewhat” or “very easy” to use. Our graphical depictions highlight, for example, that response rates do not typically drop off until the third block of questions. These findings have methodological significance for those who work with PWUD and other hard to reach populations.